2014
DOI: 10.5614/itbj.vad.2014.6.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Banana Bark as A Part of Acoustic Design Unit by Hybrid Technology Application

Abstract: Abstract. Banana bark is one of tropical indigenous natural resources that can be used as main material for many products. Being a fast-growing renewable material, it is durable and has natural patterns that people find visually attractive. Naturally, its textures and patterns are its main values; therefore it has the potential to be developed further. This research is needed to optimize the growth of small craft industries of banana bark, including the community where production activities take place, and als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…Data pisang Indonesia diharapkan dapat membantu perkembangan industri pangan berbasis pisang, agroindustri, industri kreatif dan produk berbasis pisang lainnya yang lebih terarah di seluruh Indonesia. Sebagai contoh produk turunan pisang yang dapat dimanfaatkan saat ini yaitu pembuatan material peredam suara dari pelepah pisang yang selama ini belum dimanfaatkan secara optimal (Permanasari et al, 2014). Pemanfaatan seluruh bagian tanaman pisang dapat dimanfaatkan dalam upaya mengaplikasikan zero waste pada industri pisang dan meningkatkan pendapatan Indonesia sebagai salah satu penghasil pisang terbesar di dunia.…”
Section: Data Pisang Indonesiaunclassified
“…Data pisang Indonesia diharapkan dapat membantu perkembangan industri pangan berbasis pisang, agroindustri, industri kreatif dan produk berbasis pisang lainnya yang lebih terarah di seluruh Indonesia. Sebagai contoh produk turunan pisang yang dapat dimanfaatkan saat ini yaitu pembuatan material peredam suara dari pelepah pisang yang selama ini belum dimanfaatkan secara optimal (Permanasari et al, 2014). Pemanfaatan seluruh bagian tanaman pisang dapat dimanfaatkan dalam upaya mengaplikasikan zero waste pada industri pisang dan meningkatkan pendapatan Indonesia sebagai salah satu penghasil pisang terbesar di dunia.…”
Section: Data Pisang Indonesiaunclassified
“…Permanasari, M.D [21]. revealed that banana bark's porous characteristics could potentially be improved as an acoustic material.…”
mentioning
confidence: 99%